2018
DOI: 10.1159/000486576
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Bevacizumab Combined with Mitomycin C or 5-Fluorouracil in Primary Trabeculectomy: A Meta-Analysis of Randomized Clinical Trials

Abstract: Aim: The objective of this study was to evaluate the efficacy and safety of bevacizumab combined with antimetabolite as an adjunctive therapy in primary trabeculectomy for glaucoma. Materials and Methods: PubMed, Cochrane Library, and EMBASE were searched for relevant randomized controlled trials. Efficacy was evaluated by the postoperative mean intraocular pressure (IOP), complete success, and qualified success rates. Safety was evaluated by postoperative complications and surgical interventions. Results: A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…In order to improve success rate, antimetabolites primarily mitomycin‐C (MMC) and 5‐fluorouracil (5‐FU) have been introduced in trabeculectomy. However, the application of antimetabolites also increases the risk of bleb leakage, toxic epitheliopathy, prolonged hypotony, blebitis or even endophthalmitis (Collignon‐Brach 1993; Smith et al 1994; Chen et al 2018). Many foreign biomaterials, such as horse hair, silk threads, nylon, gelatin, amniotic membrane and silicone tubes, have also been implanted in glaucoma surgery to aid filtration, but availability issues and cost factors exist.…”
Section: Biomedical Engineering Perspectivesmentioning
confidence: 99%
“…In order to improve success rate, antimetabolites primarily mitomycin‐C (MMC) and 5‐fluorouracil (5‐FU) have been introduced in trabeculectomy. However, the application of antimetabolites also increases the risk of bleb leakage, toxic epitheliopathy, prolonged hypotony, blebitis or even endophthalmitis (Collignon‐Brach 1993; Smith et al 1994; Chen et al 2018). Many foreign biomaterials, such as horse hair, silk threads, nylon, gelatin, amniotic membrane and silicone tubes, have also been implanted in glaucoma surgery to aid filtration, but availability issues and cost factors exist.…”
Section: Biomedical Engineering Perspectivesmentioning
confidence: 99%
“…Some studies examine the efficacy of Bevacizumab, an anti-VEGF drug, alone or together with MMC against post-surgical fibrosis. These experiments showed that combination of both substances did not cause more benefit than using MMC alone [41]. Also, Bevacizumab alone was not more efficient than MMC alone in inhibiting fibrosis after trabeculectomy [42].…”
Section: Discussionmentioning
confidence: 92%
“…Comparison of differences in the mean IOP between the two groups did not reveal a significant difference between the two groups; either at Month 6 (p = 0.277), Month 9 (p = 0.564) or at 1 year (p = 0.256); although the mean IOP in the 5-FU + Bevacizumab group was lower on all occasions. 14.33 ± 4.57 [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] 13.86 ± 4.22 [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] 14.5 ± 5.04 Trabeculectomy with 5-FU ø + S/C ¤ Bevacizumab Mean 28.9 ± 18.9 [Maximum 78] [Minimum 14] 12.8 ± 3.89 [5][6][7][8][9][10][11][12][13][14][15][16]…”
Section: Resultsmentioning
confidence: 99%
“…Cheng 10 et al in 2016, searched extensively in the electronic database for randomized controlled trials comparing subconjunctival bevacizumab to other antimetabolites, and concluded that there is inadequate and low quality evidence to recommend or negate its use for wound modulation in GFS. Chen and coworkers 25 in their meta-analysis in 2018, concluded that adjunctive use of bevacizumab (1.25 mg/mL) with a regular concentration of antimetabolites (5-FU or MMC) did not show any advantage or detrimental effect when compared with using antimetabolites alone.…”
Section: Discussionmentioning
confidence: 99%